Succinylcholine Use and Dantrolene Availability for Malignant Hyperthermia Treatment: Database Analyses and Systematic Review. (January 2019) - Larach, Marilyn Green; Klumpner, Thomas T.; Brandom, Barbara W.; Vaughn, Michelle T.; Belani, Kumar G.; Herlich, Andrew; Kim, Tae W.; Limoncelli, Janine; Riazi, Sheila; Sivak, Erica L.; Capacchione, John; Mashman, Darlene; et al.
Editor's Perspective: What We Already Know about This Topic: Dantrolene effectively treats malignant hyperthermia, but there are discrepant recommendations for dantrolene availability in facilities that stock succinylcholine for airway rescue but do not use volatile anesthetics. What This Article Tells Us That Is New: The authors performed an analysis of data from three databases and a systematic literature review. Providers frequently use succinylcholine, including during difficult mask ventilation. Succinylcholine given without volatile anesthetics triggered 24 malignant hyperthermia events, 13 of which were treated with dantrolene. Fourteen patients experienced substantial complications, and one died. Delayed dantrolene treatment worsened patient outcomes. Background: Although dantrolene effectively treats malignant hyperthermia (MH), discrepant recommendations exist concerning dantrolene availability. Whereas Malignant Hyperthermia Association of the United States guidelines state dantrolene must be available within 10 min of the decision to treat MH wherever volatile anesthetics or succinylcholine are administered, a Society for Ambulatory Anesthesia protocol permits Class B ambulatory facilities to stock succinylcholine for airway rescue without dantrolene. The authors investigated (1) succinylcholine use rates, including for airway rescue, in anesthetizing/sedating locations; (2) whether succinylcholine without volatile anesthetics triggers MH warranting dantrolene; and (3) the relationship between dantrolene administration and MH morbidity/mortality. Methods: The authors performed focused analyses of the Multicenter Perioperative Outcomes Group (2005 through 2016), North American MH Registry (2013 through 2016), and Anesthesia Closed Claims Project (1970 through 2014) databases, as well as a systematic literature review (1987 through 2017). The authors used difficult mask ventilation (grades III and IV) as a surrogate for airway rescue. MH experts judged dantrolene treatment. For MH morbidity/mortality analyses, the authors included U.S. and Canadian cases that were fulminant or scored 20 or higher on the clinical grading scale and in which volatile anesthetics or succinylcholine were given. Results: Among 6, 368, 356 queried outcomes cases, 246, 904 (3.9%) received succinylcholine without volatile agents. Succinylcholine was used in 46% (n = 710) of grade IV mask ventilation cases (median dose, 100 mg, 1.2 mg/kg). Succinylcholine without volatile anesthetics triggered 24 MH cases, 13 requiring dantrolene. Among 310 anesthetic-triggered MH cases, morbidity was 20 to 37%. Treatment delay increased complications every 10 min, reaching 100% with a 50-min delay. Overall mortality was 1 to 10%; 15 U.S. patients died, including 4 after anesthetics in freestanding facilities. Conclusions: Providers use succinylcholine commonly, including during difficult mask ventilation. Succinylcholine administered without volatile anesthetics may trigger MH events requiring dantrolene. Delayed dantrolene treatment increases the likelihood of MH complications. The data reported herein support stocking dantrolene wherever succinylcholine or volatile anesthetics may be used. Abstract : The authors performed an analysis of data from three databases and a systematic literature review. Providers frequently use succinylcholine, including during difficult mask ventilation. Succinylcholine given without volatile anesthetics triggered 24 malignant hyperthermia events, 13 of which were treated with dantrolene. Fourteen patients experienced substantial complications, and one died. Delayed dantrolene treatment worsened patient outcomes.Supplemental Digital Content is available in the text.